Medical Audit of the Management of Patients with Sepsis in the Intermediate Care Unit of Department Internal Medicine School of Medicine Airlangga University/Dr. Soetomo Hospital - Hadi, Usman; Triyono, Erwin Astha (Institute of Topical Disease, 2010)
Sepsis and septic shock is one of the highest causes of death in patients treated in hospitals. Research Objectives: to evaluate the quality of the management of sepsis patients in Intermediate Care Unit, Department of Internal Medicine Dr. Soetomo Hospital Surabaya, Indonesia. This study was a retrospective study to re-evaluate the patient medical record. The number of patients treated: 275 patients, sepsis patients: 80 patients, the number of patients who entered the study 50 patients, 30 (60%) female and 20 (40%) men, most age groups aged 60 -70 years (32%), Mean 54 Median 56. Diagnostic accuracy according to the criteria of sepsis 45 (90%) patients, compliance with taking blood culture 2 (4%) patients, appropriate antibiotic selection 49 (98%) patients, the number of patients who should not be given antibiotics (4 patients), but given the antibiotic is 3 (75%) patients, the number of patients who should be given antibiotics (46 patients) but were not given antibiotics 1 (2%) patient. The reason of patients discharged: 27 had died (54%), 13 cured (26%), not yet recovered 10 (20%). The reason of patients discharged forcibly: to feel recovered 2 (20%), the condition gets worse 3 (30%), no cost 2 (20%), not clear 3 (30%). Patients with sepsis remain a big problem, and it still needs to improve the management of sepsis on existing guidelines.